(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Most of the modern computer networks encounter a lot of problems in order to use the new development of technologies with its needed and requirements, especially for data density, which affect to the large data Losses, this leading to the collapse of the economy . The spread ofsocial networking including thehuge connection between users led a positively effect to the economy in the word, while if there is a user’scut ofthe social network will led a big loss in all academic life and economic.